O diálogo entre o conhecimento científico e o saber popular sobre peixes por pescadores e professores de escolas públicas localizadas na planície de inundação do alto rio Paraná - Riva, Poliana Barbosa da (2012)
Artisan fishermen have a traditional ecological knowledge, built by generation by generation, about natural history, behavior and popular classification of the fish, which is used in fishing strategies and can be useful for sustainability of fish stocks. This research's aim was to know the traditional knowledge, more specifically, the Paraná River floodplain fishermen's ethnoichthyological knowledge about ecology and local ictiofaunistic as well as to investigate how the teachers of the region promote the dialog between popular and scientific about fish with their students. The ethnoichthyological data were obtained by usual procedures of the qualitative research: interviews, recordings, observations and documental analysis. In a second moment, these information subsidize the planning and realization of a course of continuing education for the local teachers about the region's fish and ecology and the survey of their conceptions and pedagogic practices about the theme. The methodology of the data collect adopted in this phase had its base in participative research. The result obtained show that the interviewed fishermen, although they don't have access to systematized knowledge about ecology and dynamic of the floodplain, present knowledge and perception which must be considered in the environmental educational projects and the management of natural resources. Regarding to the teachers, it was observed that in spite of their initial limitations about working the knowledge dialog, as found in the questionnaire's analysis, they were rendered problematic and overcame during the course. The didactic strategies expressed in the didactic sequences performed by the teachers, at the end of the course, showed positive perspectives that both knowledge - scientific and traditional - may be worked by them, to establish a fertile dialog among different knowledge and, as a consequence, increase the critical view of the students about the environmental reality they live in.